The The Influence of Economic Growth, Education and Health on Poverty in East Java Province - Ifa, Khoirul Ifa; Al Maidah, Firdaus (OECONOMICUS Journal of Economics, 2023)
The problem studied in this study is, How does economic growth, education and health influence poverty in East Java Province. The purpose of this study was to determine the effect of economic growth, education and health on poverty in East Java Province. The research method used is using Panel Data Analysis, by choosing the best model, namely comment effect, fixed effect and random effect, selecting the best regression model using the Chow test, Hausman test and LM test. The results showed that economic growth has an effect on poverty, education also has an effect on poverty and health also has an effect on poverty.